Account receivable strategy in handling receivables’ goods at the aruss hotel semarang - Marisa, Kintan; Rahayu, Emik (Surya Hijau Manfaat, 2025)
Hotel Aruss Semarang has various payment methods that can be used by its customers. The account receivable is responsible for all transactions that are not in the form of cash. After the event ends, the accounts receivable section will send an invoice that must be paid before the due date. However, there are invoices that are past due so they require an account receivable role. The Problem of the research is what strategies are carried out by the accounts receivable section in handling receivables and the obstacles faced in the receivables collection process. Qualitative descriptive methods were used to obtain reliable data, researchers carried out observation, interviews and documentation activities. The results of this research are that the accounts receivable section has a strategy such as reminding receivables that are past due three times, if they are still not paid, the accounts receivable section together with the relevant sales person will make a visit. If payment has not been made in accordance with hotel policy, the relevant sales party will pay the receivable. The obstacles experienced by the accounts receivable section in the receivables collection process are internal obstacles and external obstacles.